Pengaruh Penambahan Jahe terhadap Karakteristik Fisik dan Penerimaan Sensori Teh Cascara Berbahan Kulit Kopi Robusta - Raihan Athallah Mukhti; Sandi Asmara; Febryan Kusuma Wisnu; Warji Warji (abe.fp.unila.ac.id, 2026)
This study evaluated the effect of ginger addition on the physical characteristics and sensory acceptance of cascara tea produced from Robusta coffee pulp. Coffee pulp is an agricultural by-product that can be processed into a value-added beverage product. Ginger was added to improve the sensory profile of cascara tea, particularly aroma and taste. The study used a single-factor Completely Randomized Design with six ginger concentrations, namely 5%, 10%, 15%, 20%, 25%, and 30% based on the weight of cascara. Each treatment was repeated three times. The observed parameters included moisture content, specific gravity, sediment content, and sensory acceptance. The results showed that ginger concentration significantly affected moisture content, but did not significantly affect specific gravity and sediment content. Sensory evaluation showed that the addition of 10% ginger produced the highest acceptance score compared with other treatments. Excessive ginger concentration tended to reduce panelist preference because the pungent ginger flavor became dominant. Based on the observed physical and sensory characteristics, the addition of 10% ginger was considered the most acceptable formulation for cascara tea made from Robusta coffee pulp. Further studies are required to analyze bioactive compounds, antioxidant activity, microbial safety, and storage stability before the product can be claimed as a functional beverage.